THE EFFECT OF WORK LIFE BALANCE AND JOB SATISFACTION ON TURNOVER INTENTION OF NON ASN WITH RESILIENCE AS A MODERATOR VARIABLE - Andi Ricardy Purba; Syahrizal Bin Muhammad Syafii (PT. Jurnal Center Indonesia Publisher, 2026)
Tujuan penelitian ini adalah untuk menganalisis dan menguji pengaruh work life balance dan kepuasan kerja terhadap turnover intention pegawai Non ASN Kabupaten Banyuasin. Selain itu, penelitian ini bertujuan untuk mengetahui seberapa besar peran resiliensi dalam memoderasi hubungan antara work life balance dan kepuasan kerja terhadap turnover intention. Penelitian ini juga dimaksudkan untuk memberikan gambaran empiris mengenai faktor-faktor yang mempengaruhi niat pegawai Non ASN dalam meninggalkan pekerjaan. The purpose of this study is to analyze and test the influence of work life balance and job satisfaction on the turnover intention of Non-ASN employees in Banyuasin Regency. In addition, this study aims to find out how much role resilience plays in moderating the relationship between work life balance and job satisfaction to turnover intention. This study is also intended to provide an empirical picture of the factors that affect the intention of Non-ASN employees in leaving their jobs. The results of the research are expected to be a basis for consideration for the Banyuasin Regency Government in formulating policies that improve the welfare, loyalty, and stability of the performance of Non-ASN employees. This study uses a quantitative approach with a type of causal associative research. With a population of 6,120 Non-ASN employees and an error rate of 5%, the number of samples needed is 376 respondents. Data analysis was carried out using the help of SmartPLS statistical software. Based on the results of the study, Work Life Balance and Job Satisfaction have a negative and significant effect on the Turnover Intention of Non-ASN employees in Banyuasin Regency. The better the work-life balance and the higher the job satisfaction, the lower the employee's intention to leave. Job satisfaction is the most dominant factor. In addition, resilience acts as a moderator that strengthens the negative influence of the two variables, so that it is able to suppress the tendency of turnover intention more effectively